Using Science and Technology- Based Community Learning Model Through the Natural Environment Exploration Approach:Increasing the Motivation and Positive Science Attitude - Yustina, Yustina; Dahnilsyah, Dahnilsyah (Proceedings of the UR International Conference on Educational Sciences, 2018)
This aims to explorestudentsâ motivation and scientific attitudes using the learning model of STCthrough the natural environment exploration approach inSenior High School 1, Kampar. It is an action research which was conducted from April to June 2018. Participants of this research were 34 students of the tenth grade,Mathematics and Natural Science students, odd semester, comprising 8 males and 26 females. The parameters of this research were motivation and attitudes. The result of this study demonstrates that the motivation and attitudes towards science have significant improvements. It shows that the studentâs learning motivation has improved from 6,41% in the first cycle to 10,56% in the second cycle. At the average, in the first cycle, the score of scientific attitudes was 3,58 (category A- (B). In the second cycle, it had increased to 3,90 which was categorized into A. Based on the result of this study, it can be concluded that the application of the learning model of STCusing the natural environment exploration strategy is effective to improve the motivation and positive attitudes towards science of the tenth grade students ofMathematics and Natural Science, State Senior High School 1, Kampar.